Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2470725
|View full text |Cite
|
Sign up to set email alerts
|

At the interface of biology and computation

Abstract: Representing a new class of tool for biological modeling, Bio Model Analyzer (BMA) uses sophisticated computational techniques to determine stabilization in cellular networks. This paper presents designs aimed at easing the problems that can arise when such techniques-using distinct approaches to conceptualizing networks-are applied in biology. The work also engages with more fundamental issues being discussed in the philosophy of science and science studies. It shows how scientific ways of knowing are constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…where E "./ is the critical electrical field at velocity saturation point and L is the length of the transistor. The gate drive voltage of transistor M is proportional to I " , hence I " is limited by I " and is given as Equation (5).…”
Section: Proposed Analog Electronic Models For Hill Processmentioning
confidence: 99%
“…where E "./ is the critical electrical field at velocity saturation point and L is the length of the transistor. The gate drive voltage of transistor M is proportional to I " , hence I " is limited by I " and is given as Equation (5).…”
Section: Proposed Analog Electronic Models For Hill Processmentioning
confidence: 99%
“…Kuznetsov et al [29] have envisioned DIYbio platforms in HCI as rich tools for expertise sharing as well as instruments for public engagement with science. Taylor et al [44] explored a computational biology tool from an HCI perspective and suggested that the conceptual problems that exist when using tools that model biology can be seen as opportunities to view design and HCI within an orientation that contests science as a monistic endeavor and supports instead an emergent idea of scientific ways of knowing. Kim et al [26] developed the LudusScope, a smartphone-compatible DIY microscope that enables HBI.…”
Section: Human-computer Interaction In the Life Sciencesmentioning
confidence: 99%
“…Thus, participation in genetics is often motivated by and brings about a host of new concerns, from discovering personal and intimate information about oneself to understanding patterns in human migration and evolution. These issues reflect opportunities and challenges arising from the convergence of biology and computation [27].…”
Section: Introductionmentioning
confidence: 99%